Jala karya titis basino - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
ABSTRACT This research aims to reveal the meaning conveyed by the author through signs in the novel Iola using theory of Riffaterre's semiotics. The method used, Semiotics of Riffaterre, sees a literary works as a semiotic phenomenon. In that method, there are four things that should be considered in understanding a literary work, i.e. a poem or literary work that expresses something indirectly, heuristic and hermeneutic reading, matrix, model, and variance, and hypogram in the literary work. Data are taken from pia, a novel written by Titis Basino P.I. From the heuristic reading, it is concluded that the story consists of three parts, namely